Analisis Pengaruh Kredibilitas Endorses DAI Dalam Iklan Terhadap Minat Beli Pada Produk Telkomsel - Kiki Wulandari (Bahtera Inovasi, 2020)
This research aimed to examine the effect of the attractiveness, trustworthiness, expertise toward attitude toward advertisement and attitude toward advertisement toward purchase intention. The research respondent were the people in DIY who use Telkomsel provider. Data were analized with AMOS. The result of analyze showed that the attractiveness had a significant influence to attitude toward advertisement, trustworthiness had a significant influence to attitude toward advertisement, expertise had a significant influence to attitude toward advertisement, attitude toward advertisement had a significant influence to purchase intention.